Prevalence, Knowledge, and Attitude Toward Electronic Cigarette Among Female Students in Saudi Arabia. A Cross-Sectional Study - Alrajeh, leena; Alhumud, Manal (Archives of Clinical and Biomedical Research, 2024)
Objective: The purpose of this study was to analyse and compare female students' knowledge, perception, and attitude regarding electronic cigarette ECs, as well as the prevalence of EC use. Methods: A self-report survey collected data from 391 female students above the age of 18, smokers and non-smokers. The participants enrolled in this study were female students enrolled in various colleges at King Saud University. Results: In total, 9.5% of them admit being smokers, with 3.8% of them were from health sciences college which represent 40.5% of all smokers; 2.8 % of participants quit smoking and mare than half of them from Health colleges; while the rest of participants who are non-smokers were mainly from community colleges. 15.6% of participants used EC just for leisure while 3.6% used it as a recreational program to quit smoking. Regarding tested knowledge about some adverse effect of EC use, [63.7%] have no idea about the content of EC vapor but the majority believe that it causes addiction and 64.2 % agreed that it is carcinogenic. Conclusion: Early education about EC hazards on health and its uselessness effect on quitting smoking can increase awareness but not enough motivation to quit smoking. The prevalence of EC use was found to be higher also among traditional smokers and previous smokers due to false believe that it helps in smoking cessation while the majority of EC user and non-user believe that it's just a leisure and show. Knowledge about the vapor content is quit less in majority of students.